The effect of heat polymerized-acrylic resin disinfected with sodium hypochlorite and castor oil (Ricinus communis oil) colour stability - Gandhi, Kavita; Ritonga, Putri Welda Utami (Padjadjaran Journal of Dentistry, 2021)
Introduction: The 1% sodium hypochlorite and Castor oil are disinfectants which show good bactericidal and fungicidal properties, although sodium hypochlorite is more commonly used. However, the use of 1% sodium hypochlorite could influence the color stability. In other hands, Castor oil does not cause any significant changes on the color stability of the acrylic resin. This research, therefore, was aimed to analyse the effect of heat polymerized acrylic resin base disinfection with sodium hypochlorite and castor oil (Ricinus communis) oil on colour stability. Methods: This research was laboratory experimental research. The total of 30 samples was determined by using Federer’s formula, divided into 3 groups with different disinfection treatment: Group A (1% Sodium Hypochlorite); Group B (10% Castor oil (Ricinus communis); and Group C (distilled water) as control group. The sample was obtained from the master model based on the ADA No.12 specification and was needed to calculate color stability. All data was then statistically analysed with the Kruskal-Wallis test, followed by an LSD test. The measurement of color stability was performed using a UV-Vis Spectrophotometer following the Beer-Lambert Law. Results: Color stability results for group A, B, and C were 0.059 ± 0.038, 0.105 ± 0.041 and 0.136 ± 0.052, consecutively. The Kruskal-Wallis test results obtained a significance level of p = 0.005 (p < 0.05) indicated a difference in the color stability of heat polymerized acrylic resin denture after disinfected with 1% sodium hypochlorite and 10% castor oil. Disinfection of 1% sodium hypochlorite causes the change in the colour stability of the heat polymerized acrylic resin compared to the control group, while disinfection of 10% castor oil did not. There was found a significant difference in the colour stability of the heat polymerized acrylic resin between disinfection with 1% sodium hypochlorite and 10% castor oil (p = 0.027 < 0.05). Conclusions: The colour stability of heat polymerized acrylic resin is not changed after disinfection with 10% Castor (Ricinus communis).